Quality and Reliability of Raynaud's Phenomenon Information on YouTube: A Cross-Sectional Study - Albayrak, Fatih; Oz, Burak (Pera Yayincilik Hizmetleri, 2025)
Objective: Raynaud's phenomenon, impacting small blood vessels, can be triggered by cold or emotional stress and present as a primary disorder or a symptom of other diseases. Given the growing use of platforms like YouTube for health information, assessing the reliability of Raynaud's phenomenon videos is crucial. This study aimed to assess the quality, reliability, and educational merit of YouTube videos about Raynaud's phenomenon. Methods: A YouTube search was performed on February 10, 2025, including videos uploaded since 2012. YouTube search utilized keywords like 'Raynaud's phenomenon', 'Raynaud's syndrome', 'Primary Raynaud's disease', 'Secondary Raynaud's disease', 'Primary Raynaud's phenomenon', 'Secondary Raynaud's phenomenon' and 'Raynaud's disease'. The Global Quality Scale (GQS), modified DISCERN, and a usefulness scale were used by two independent raters to assess video content characteristics. Results: 100 videos underwent evaluation. The GQS assessment revealed 49 highquality videos (49%), 23 intermediate-quality videos (23%), and 28 low-quality videos (28%). Modified DISCERN and GQS scores showed a strong positive correlation (r = 0.709, p <0.001), while popularity measures did not significantly correlate with quality scores. Raynaud's phenomenon information on YouTube is unreliable and inconsistent; videos created by rheumatologists have the highest quality. Conclusion: Healthcare professionals should direct patients to trustworthy sources, develop evidence-based materials to enhance the quality of online health information, and seek collaboration with other healthcare professionals. The overall quality of Raynaud's phenomenon-related YouTube videos was found to be highly variable, with nearly half rated as high quality, while a significant portion lacked sufficient reliability and educational value.
Keywords: health information; Raynaud's phenomenon; Raynaud's disease; social media; YouTube; quality assessment